Phenotypic and Morphometric characterization of indigenous chickens at Jhenaigati upazila of Sherpur district in Bangladesh (SAARC Journal of Agriculture, 2015)
The study was conducted at Rangtia, Shalchura and Dudhnoi villages under Jhenigati upazilla of Sherpur district in Bangladesh for phenotypic and morphometric characterization of indigenous chickens. Among three types of indigenous chickens, Non-descript Deshi were prominent (86%), compared to Cap Headed (10%) and Naked Neck (4%) and the overall mean body weight, back length, body circumference and pelvis width were 961.50 ± 17.79 gm, 152.70 ± 1.29 mm, 219.20 ± 1.89 mm and 25.57 ± .62 mm respectively. The prominent colors of plumage, shank, skin, earlobe and eggshell were multiple (24%), white (52%), white (89%), white & red (47%) and white (48%), respectively while 99% chickens had single comb. The highest correlation (0.70) was observed between body weight & body circumference followed by (0.36) between body weight & back length and (0.27) between body weight & pelvis width while eggshell color was significantly correlated with body weight (-0.48), body circumference (-0.41) and pelvis width (-0.26). However, comb type was significantly (p